Crohn Disease Infrequently Affects the Appendix and Rarely Causes Granulomatous Appendicitis. (13th December 2021) - Mostyka, Maria; Fulmer, Clifton G.; Hissong, Erika M.; Yantiss, Rhonda K.
Abstract : Data from previous studies suggest Crohn disease of the appendix accounts for ∼25% of granulomatous appendicitis cases. However, we have found that granulomatous inflammation in appendectomy specimens rarely heralds Crohn disease. We suspect that appendiceal involvement by Crohn disease is uncommon, even when patients have severe ileocolonic inflammation. We performed this study to determine the prevalence and nature of appendiceal inflammation among patients with Crohn disease. We reviewed 100 ileocolic specimens with strictures and fistulizing Crohn disease for the nature and distribution of inflammatory changes in the appendix and compared them with 100 appendices on colectomy specimens from age-matched and sex-matched patients with ulcerative colitis. We also evaluated 27 additional cases of granulomatous appendicitis in appendectomy specimens to determine the frequency with which this finding represented Crohn disease. The appendix was usually normal (26%) or showed fibrous obliteration (50%) in ileocolic resection specimens from patients with Crohn disease. Mucosal inflammation was much less common in appendices from patients with Crohn disease than ulcerative colitis (6% vs. 28%, P <0.0001); only 4 cases contained epithelioid granulomata, 3 showed mural fibrosis and lymphoid aggregates, and 10 displayed only periappendiceal inflammation. None of the patients with granulomatous appendicitis in appendectomy specimens had, or developed, evidence of Crohn disease. We conclude that Crohn disease infrequently affects the appendix. Interval appendectomy and infection are more important considerations when appendectomy specimens feature granulomatous inflammation and/or mural lymphoid aggregates, especially if there is no history of idiopathic inflammatory bowel disease.